Pasaog SurutTer mloal Klllran Jao Dl Ka bupatcn Sijunjun g Tahun 1994-2013 - Ningsih, Wiwin Sulastri (Pendidikan Sejarah, 2014)
K ilir.1n Jao renninal was opcring at 1994, I)Ccember 24. l11is tescarch is U.<;(.l to telcal lhc pre$C!nting the S""up :.lnd devdupmcnt or Kilir.tn Jao 1ctmit1al. The grow up and development or ahe arco. c3n be seen from many sector. such as trans:portation part. which has $ r()n{l. relationship with soc al tr.aOic andcconom), 1his n:scarch hJS three purpOseS. they are : to desctibc the bui1ding or K ilirnn Joo background. lOde$cribc how the activilv in Kilimn Jao Tcrmin31.and to describe the effect ()f K iliron J:lo Tcrminal towurd thegocrnmcnt and JX!(-.plc.duving 1994·2013 year. The method used in this research is history mcthexl b) usingsteps heuriStic (collecting the needed sources in 1his research). sou rces t-risti$11"1, interprew.tion and hiMoriograph), The rchcr found th rL-e phenomena in this rc an:h. th ey are: firs is Kiliro.n Jao tcnnin als is the im.-.,m c of tht: people Qround this arc!t in Kiliron Jao. Second. Kiliran Jao tcrmin:tl is also a gig don:u or in commnicu.tioo sc.«:tor.Threc.1he Kilirnn Jao termi nal get upS an d do"ns since it was operated every yc rs h is because the vehicle is unconstant to entel lhis tcnninaJ ever) da) . From lhis n...-..corch. it i$ oonclude that thepresent of Kilimn Jao tenni nal is the inoome of the JX!Oplc Q.rOOnd K ilintn Jao and eon help the economy orthem . altough it is not spread. Kilir.lll Jao Terminal became :t new job held   lOr the people who \(ni;.S ininlorma.J  sector such a.o; trader and sctrice seller. J"hc income from  Kilirnn  Jao Tenninal  restribution get u p:-.do\ OS every years.